Research Centre At Belum - RM78mil biodiversity and biotechnology centre will create job opportunities - The Star, (2008)
A Belum Valley Biodiversity and Biotechnology Centre will be set up to research and develop the natural resources of Royal Belum one of the world s oldest tropical rain forests.